The The Effect of Service Quality and Customer Satisfaction on Customer Loyalty - Rorim Panday; Muhammad Fadhli Nursal (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to know how service quality and customer satisfaction affect McDonald's customer loyalty. The object of this research is McDonald's fast food Restaurant. This type of research is quantitative and analysis techniques using multiple linear regression. The sample of this study was 210 respondents who were selected by the convenience sampling method. The results of this study are that Service Quality and Customer Satisfaction partially and simultaneously have a positive and significant effect on Customer Loyalty. Therefore, McDonald supposes that customers consider fast service, so they should minimize customer queues, to provide better price quotes to customers, and Mc Donald should continue to improve the quality of its services.